Malaysian legal system: an introduction - Ali Mohamed, Ashgar Ali (CLJ Publication, 2020)
In order to understand how the Malaysian legal system has evolved and why it changed, it is necessary to discuss the Malaysian legal history. In fact, knowledge of the legal history provides the foundation from which one can begin to understand and apply the principles of constitutional, administrative, and judicial law, among others. As noted earlier, the legal system of Malaysia is based mainly on the English common law tradition which was a direct result of the British occupation of Malay States and the Borneo States in early 19th century right up to the early 1960s. The early laws of the Malay States are recorded from the time of the Malacca Sultanate in the 15th century